CHARACTER-BASED LEARNING AND SELF-DEVELOPMENT TO IMPROVE THE STUDENTS’ CHARACTER EDUCATION - Samsinar Samsinar; Fitriani Fitriani (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
Abstract:This study aimed to describe character-based learning, to identify self-development forms, to find out the application of character education, and to find out whether there was a significant influence between character-based learning and self-development in improving the students’ character education at Islamic Junior High School in Bone Regency. The method used was mixed-method. The sample of this research consisted of 50 students. The instruments used were questionnaire, observation guidelines, interview and document. The findings indicated that the implementation of character education was carried out through inculcating values, exemplary values, facilitation, academic activities, social, and religious activities. The application of self-development activities was done through routine, spontaneous, exemplary, programmed activities and conditioning. The character education was carried out through the application of class-based character education, school culture, and community-based character education activities. Therefore, there was a significant influence between the character-based learning process and self-development activities on improving the students’ character.Abstrak:Penelitian ini bertujuan untuk mendeskripsikan pembelajaran berbasis karakter, mengidentifikasi bentuk-bentuk pengembangan diri, mengetahui penerapan pendidikan karakter, dan mengetahui apakah ada pengaruh yang signifikan antara pembelajaran berbasis karakter dan pengembangan diri dalam meningkatkan pendidikan karakter siswa pada SMP Islam di Kabupaten Bone. Kombinasi metode penelitian kualitatif dan kuantitatif digunakan dalam penelitian ini. Sampel penelitian ini terdiri dari 50 siswa. Instrumen yang digunakan adalah kuesioner, pedoman observasi, wawancara dan dokumen. Hasil penelitian ini menunjukkan bahwa pelaksanaan pendidikan karakter dilakukan melalui penanaman nilai-nilai keteladanan, fasilitasi, dan kegiatan pengembangan akademik, sosial dan keagamaan pada SMP Islam di Kabupaten Bone. Penerapan kegiatan pengembangan diri melalui kegiatan rutin, spontan, keteladanan, kegiatan terprogram dan pengkondisian. Pendidikan karakter dilakukan melalui penerapan pendidikan karakter berbasis kelas, budaya sekolah, dan kegiatan pendidikan karakter berbasis masyarakat. Oleh karena itu, terdapat pengaruh yang signifikan antara proses pembelajaran berbasis karakter dan kegiatan pengembangan diri pada peningkatan karakter siswa.